Thick Red Tape and the Thin Blue Line: A Field Study on Reducing Administrative Burden in Police Recruitment. (14th November 2019) - Linos, Elizabeth; Riesch, Nefara
Abstract: Police departments struggle to recruit officers, and voluntary drop‐off of candidates exacerbates this challenge. Using four years of administrative data and a field experiment conducted in the Los Angeles Police Department, the authors analyze the impact of administrative burden on the likelihood that a candidate will remain in the recruitment process. Findings show that reducing friction costs to participation and simplifying processes improve compliance, as behavioral public administration would predict. Applicants who were offered simpler, standardized processes completed more tests and were more likely to be hired. Later reductions to perceived burden led to an 8 percent increase in compliance, with a 60 percent increase in compliance within two weeks. However, removing steps that would have allowed for better understanding of eligibility kept unqualified candidates in the process for longer, reducing organizational efficiency. These results extend the field ' s understanding of how administrative burden can impact the selection of talent into government .